Recent Advances in Videolaryngoscopy for One-Lung Ventilation in Thoracic Anesthesia: A Narrative Review - Yao, Wenlong; Li, Meihong; Zhang, Chuanhan; Luo, Ailin (Frontiers in Medicine, 2022)
Since their advent, videolaryngoscopes have played an important role in various types of airway management. Lung isolation techniques are often required for thoracic surgery to achieve one-lung ventilation with a double-lumen tube (DLT) or bronchial blocker (BB). In the case of difficult airways, one-lung ventilation is extremely challenging. The purpose of this review is to identify the roles of videolaryngoscopes in thoracic airway management, including normal and difficult airways. Extensive literature related to videolaryngoscopy and one-lung ventilation was analysed. We summarised videolaryngoscope-guided DLT intubation techniques and discussed the roles of videolaryngoscopy in DLT intubation in normal airways by comparison with direct laryngoscopy. The different types of videolaryngoscopes for DLT intubation are also compared. In addition, we highlighted several strategies to achieve one-lung ventilation in difficult airways using videolaryngoscopes. A non-channelled or channelled videolaryngoscope is suitable for DLT intubation. It can improve glottis exposure and increase the success rate at the first attempt, but it has no advantage in saving intubation time and increases the incidence of DLT mispositioning. Thus, it is not considered as the first choice for patients with anticipated normal airways. Current evidence did not indicate the superiority of any videolaryngoscope to another for DLT intubation. The choice of videolaryngoscope is based on individual experience, preference, and availability. For patients with difficult airways, videolaryngoscope-guided DLT intubation is a primary and effective method. In case of failure, videolaryngoscope-guided single-lumen tube (SLT) intubation can often be achieved or combined with the aid of fibreoptic bronchoscopy. Placement of a DLT over an airway exchange catheter, inserting a BB via an SLT, or capnothorax can be selected for lung isolation.